Motivations, behaviour and cognition of novice and habitual business angels in new firm incorporations - Farrell, A. Ellen. (2005)
Re-investment is vital to the business angel "industry" because re-investing angels endorse a greater number of entrepreneurs and invest more funds than non-reinvesting angels. In this exploratory empirical analysis, the appraisal qualities of business angels are examined relative to their impact on producing successful investments as well as their impact upon re-investment. The three appraisal qualities investigated are business angels' motivations, their deal generation behaviours and the cognitive heuristics of overconfidence and representativeness. The analysis is based on the information model of the existence of the formal venture capital industry.